Impact of histological and clinical parameters on resection status and recurrence probability in head and neck basal cell carcinomas - Deffner, Felix; Magradze, Givi; Melzer, Kia; Schlieper, Anna Charlotta; Knopf, Andreas; Mansour, Naglaa; Becker, Christoph; Ketterer, Manuel Christoph (Frontiers in Oncology, 2025)
ObjectivesThis study aims to identify histological and clinical parameters associated with an R1 resection status and the recurrence rate in surgically treated basal cell carcinomas (BCC) and to evaluate the impact of an initial R1 resection status on the likelihood of tumor recurrence. Understanding these associations is essential for optimizing surgical treatment strategies and reducing the risk of BCC recurrences.MethodsThis retrospective single-center study analyzed primary head and neck BCC surgically treated between 2019 and 2024 to evaluate patient and tumor characteristics, including histological subtype, tumor location, resection status, and recurrence rate. R0 was defined as complete excision with a safety margin of at least 3 mm or histopathological confirmation of complete tumor removal with tumor-free resection margins.ResultsAmong 241 cases of head and neck BCC, an initial R1 resection status was significantly associated with the sclerodermiform subtype and auricular localization. Tumor clearance was achieved within one or two surgical stages in approximately 80% of cases. Despite these risk factors, organ preservation was possible in over 93%, and local anesthesia proved sufficient in 90% of procedures. The recurrence rate remained low at 2.1%. Reconstructive techniques were frequently required, with local flaps and skin grafts being the most used methods.ConclusionThis study highlights the effectiveness of outpatient procedures under local anesthesia on the one hand and the tissue-sparing and organ-preserving approach on the other for head and neck BCC, achieving high R0 resection and organ preservation rates. Incomplete resection was linked to the sclerodermiform subtype and auricular location. Despite these risks, recurrence was rare. The frequent use of reconstructive techniques reflects the focus on aesthetic and functional outcomes.